Dynamics of Confined Short-Chain alkanol in MCM-41 by Dielectric Spectroscopy: Effects of matrix and system Treatments and Filling Factor - Josef Bartoš (Polymers, 2020)
The dynamics of n-propanol confined in regular MCM-41 matrix with the pore size Dpore = 40 Å, under various matrix conditioning and sample confining conditions, using broadband dielectric spectroscopy (BDS), is reported. First, various drying procedures with the capacitor filling under air or N2 influence the BDS spectra of the empty MCM-41 and the confined n-PrOH/MCM-41 systems, but have a little effect on the maximum relaxation time of the main process. Finally, various filling factors of n-PrOH medium in the optimally treated MCM-41 system lead to unimodal or bimodal spectra interpreted in terms of the two distinct dynamic phases in the confined states.